If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -5)(x + -2) = 0 Reorder the terms: (-5 + 3x)(x + -2) = 0 Reorder the terms: (-5 + 3x)(-2 + x) = 0 Multiply (-5 + 3x) * (-2 + x) (-5(-2 + x) + 3x * (-2 + x)) = 0 ((-2 * -5 + x * -5) + 3x * (-2 + x)) = 0 ((10 + -5x) + 3x * (-2 + x)) = 0 (10 + -5x + (-2 * 3x + x * 3x)) = 0 (10 + -5x + (-6x + 3x2)) = 0 Combine like terms: -5x + -6x = -11x (10 + -11x + 3x2) = 0 Solving 10 + -11x + 3x2 = 0 Solving for variable 'x'. Factor a trinomial. (5 + -3x)(2 + -1x) = 0Subproblem 1
Set the factor '(5 + -3x)' equal to zero and attempt to solve: Simplifying 5 + -3x = 0 Solving 5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 0 + -5 -3x = 0 + -5 Combine like terms: 0 + -5 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {1.666666667, 2}
| 8-5x-x=14 | | (8x-5x)+(-2-8)= | | X+(3-2x)= | | -3/4+4/-7= | | 3/4+4/7= | | -3/4+-4/7= | | 3x+4y=a | | 10x^3-7x^2-12x=0 | | 3x+12=9x+36 | | 3x+12=9x+39 | | 2(3x+4)-1=9 | | 2x+13=7x+5 | | (x+5)*(x+5)=6 | | 6x+3=7x+2 | | 7+2a=33-2a | | =x^2+3xy+2y^2 | | sqrt(5x+5)=4 | | 2x+4X-4=16 | | 3000*x=7000 | | -2-28= | | (5-v)(4v-7)=0 | | v^2-v-30=o | | .67(1+n)=-.5n | | (3v+8)(2-v)=0 | | x^4-14x^2+24x-10=0 | | 4a-8a+10=4 | | 13x-4=5x+32 | | 25.12=.3333(12.56h) | | -6a+8= | | -1+10x=15y | | 1344=L(8)(12) | | 0.003x=6 |